1987
DOI: 10.1210/jcem-65-1-53
|View full text |Cite
|
Sign up to set email alerts
|

Bone Histomorphometry in Hypogonadal and Eugonadal Men with Spinal Osteoporosis*

Abstract: We present iliac bone histomorphometric data after in vivo double tetracycline labeling and related biochemical data from 14 nonalcoholic men referred for evaluation of symptomatic spinal osteoporosis. Six patients had previously undiagnosed hypogonadism, and 8 had normal gonadal function and no evident etiology for osteoporosis. Bone histomorphometry revealed no differences in structural measurements or resorption indices between the 2 groups. However, compared to reference values for normal postmenopausal wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
5
3

Year Published

1989
1989
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(69 citation statements)
references
References 31 publications
5
56
5
3
Order By: Relevance
“…27 In this study, viral cirrhotic patients had lower serum FTI concentrations than control subjects, but we found no correlation between FTI and BMD.…”
Section: Discussioncontrasting
confidence: 64%
“…27 In this study, viral cirrhotic patients had lower serum FTI concentrations than control subjects, but we found no correlation between FTI and BMD.…”
Section: Discussioncontrasting
confidence: 64%
“…40 In hypogonadal men, the classic bone histomor- phometric findings include osteoclast activation associated with trabecular plate perforation and loss of trabecular connectivity. 41 Markers of bone turnover clearly are elevated in men after either undergoing orchidectomy or receiving ADT for prostate carcinoma. In recent studies, increases in urinary deoxypyridinoline excretion rates and telopeptide concentrations of between 150% and 200% above baseline values have been reported after the commencement of ADT, suggesting that these men lose bone at a much higher rate compared with others their age.…”
Section: Noninvasive Markers Of Bone Turnover In Normal Men and In Mementioning
confidence: 99%
“…The endpoints of these studies were BMD (5, 7, 8, 11-13, 59, 64-66, 68-80), static or dynamic histomorphometry (7, 59-62, 64, 65, 67, 68, 87, 88), measurement of biochemical markers of bone formation and bone resorption (5,12,65,66,69,(81)(82)(83)(84)(85)(86)(87)(88), or biomechanical properties of bone (63). The majority of studies were performed either in spontaneous or orchiectomy-induced hypogonadism with or without subsequent androgen replacement therapy, or androgen treatment of eugonadal male or female subjects.…”
Section: In Vivo Effects Of Androgens On Bone Metabolismmentioning
confidence: 99%
“…Profound hypogonadism is associated with increased bone resorption (81,82). Tenover (83) showed that 3 months of testosterone treatment of 13 healthy men (aged 57 to 76 years) with borderline serum testosterone levels (<400 ng/dl) resulted in a 28% reduction in urinary hydroxyproline excretion.…”
Section: Effects Of Androgens On Biochemical Markers Of Turnovermentioning
confidence: 99%